Enhancing Literary Literacy through Multimodal Representations: A Development Study of Folklore-Based Creative Puppetry - Dharlinda Suri; Andri Wicaksono; Yulia Siska; Wayan Arya Murtika; Park Jin Ryeo (FKIP Universitas Lampung, 2026)
This study aims to develop Radin Jambat Creative Puppetry as a culturally grounded instructional medium and to examine its feasibility, practicality, and potential influence on elementary school students’ literary literacy. Using the ADDIE development model, the media was validated by content, language, and design experts; tested for practicality with teachers and students; and examined using a one-group pretest–posttest design involving 62 fourth-grade students. Data included expert validation ratings, practicality questionnaires, and literary literacy test scores. Expert validation indicated high feasibility across content (92%), language (90%), and media design (94%). Teachers (93%) and students (91%) rated the medium as highly practical. Pretest–posttest comparisons showed an increase in students’ scores, and statistical analysis (t(61) = 14.27, p < .001) and the effect size (d = 1.21) indicated positive learning trends. However, causality cannot be inferred due to the research design. The Radin Jambat Creative Puppetry demonstrates promising potential as a culturally grounded, multimodal medium that may support improvements in students’ literary literacy. However, because no control group was included, the findings should be interpreted as indicative rather than conclusive. Further research using stronger experimental designs is recommended. Keywords: literary literacy, creative puppetry, Radin Jambat, elementary school students.